2011
DOI: 10.1089/jwh.2009.1831
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Mobility Impairment on the Diagnosis and Treatment of Breast Cancer

Abstract: Background: Among women with chronic, preexisting mobility impairments, we sought to explore how their mobility difficulties affected the diagnosis and treatment of early-stage breast cancer Methods: This is a qualitative analysis of transcripts from in-depth in-person or telephone interviews with 20 English-speaking women who had early-stage breast cancer, were <60 years of age, and had chronic difficulty walking or used wheeled mobility aids at the time of their breast cancer diagnoses Results: Nine women we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 28 publications
2
52
0
Order By: Relevance
“…33 Interviews with women with disabilities who had developed early-stage breast cancer found that they frequently confronted physical barriers to care, such as inaccessible examining tables, weight scales, infusion chairs, mammography machines, and radiology equipment. 35,36 For example, a woman who is paraplegic reported that the cancer clinic at a major academic medical center she was referred to did not have a weight scale that was accessible by wheelchair. A woman's weight determines certain chemotherapy dosages.…”
Section: Lifestyle Modificationmentioning
confidence: 99%
“…33 Interviews with women with disabilities who had developed early-stage breast cancer found that they frequently confronted physical barriers to care, such as inaccessible examining tables, weight scales, infusion chairs, mammography machines, and radiology equipment. 35,36 For example, a woman who is paraplegic reported that the cancer clinic at a major academic medical center she was referred to did not have a weight scale that was accessible by wheelchair. A woman's weight determines certain chemotherapy dosages.…”
Section: Lifestyle Modificationmentioning
confidence: 99%
“…Although participants’ mobility considerations influenced their decisions about surgical approach and chemotherapy [2], most women did not express that having a physical disability influenced their breast cancer treatment perspectives with regard to body image. While women were not necessarily probed explicitly about whether their disability influenced their body image, it appears that practical considerations may overshadow body-image related concerns.…”
Section: Discussionmentioning
confidence: 99%
“…This research is part of a larger published study investigating diagnosis and treatment experiences of women with physical disabilities who developed early-stage breast cancer [2, 6]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drawing upon literature reviews and our previous studies addressing health care experiences of persons with disabilities, 5,1621 we designed a semi-structured, open-ended interview protocol for this qualitative descriptive study. Qualitative descriptive studies provide comprehensive summaries of events or experiences without over interpretation of the meaning of the event or experience to study participants.…”
Section: Methodsmentioning
confidence: 99%